AMIR-HASSAN COMPLICATED RELATIONSHIP: (A SOCIO-PSYCHOLOGICAL STUDY IN KHALED HOSSEINI’S THE KITE RUNNER) - Hertiana Ikasari (Jurnal CULTURE (Culture, Language, and Literature Review), 2020)
The Kite Runner presents new idea and color, namely complexity of conflict toward friendship (characters) and other conflicts that happened in Afghanistan during colonization and post colonization era. There are relationships at the heart of The Kite Runner. The friendship between the two main characters, Amir and Hassan and the relationship between father and son are of importance in the novel. The first important relationship in the novel is the one between Amir and Hassan. This relationship is very complex. The objectives of the study are to analyze complicated relationship between Amir and Hassan on The Kite Runner novel and to analyze Socio-Psychological perceived on Amir and Hassan relationship The writer uses qualitative descriptive research. The writer uses the primary data and the secondary data. The primary data source is The Kite Runner novel as the object of the research. The secondary data were taken from books and journal articles supporting the analysis of Amir and Hassan relationship. The result shows that the factors influencing the relationship are similarity, reciprocity of liking and positive quality. The similarity between Amir and Hassan are on three things: family background, preference and complex problem. Based on J.W Thibaut and H.H Kelley’s social exchange theory, Amir and Hassan have good outcome, because it comes from the high rewards and low cost. Finally the value of Amir and Hassan’s relationship is the tied and interdependence relationship. It is represented by the formula: Outcome > CL > CL ALT it means: satisfactory, stable and interdependence. Keywords: Relationship, Socio Psychology, Social Exchange Theory, Satisfactory, Stable